Fructose 1,6 bisphosphatase deficiency mimicking glycogen storage disease as recurrent hypoglycemia - Manoj Madhusudan; Janani Sankar; Venkateswari Ramesh (Indian Pediatrics Case Reports, 2021)
Background: Fructose 1,6 Bisphosphatase (FBPase) deficiency is a rare and treatable cause of ketotic hypoglycemia in children. Affected children present in the postneonatal period with recurrent episodes of early morning hypoglycemia typically triggered by an infection. We present a child with recurrent hypoglycemic seizures who was initially considered as glycogen storage disease (GSD) type 1, but on further evaluation, was diagnosed with FBPase deficiency. Clinical Description: A 2.5-year-old developmentally normal boy presented with the second episode of hypoglycemic seizure. He had a similar episode following a fasting time of 10 h at 2 years of age. Critical sample analysis revealed ketosis, lactic acidosis, hyperuricemia, and raised triglycerides. He was diagnosed with probable GSD type 1. At 2.5 years of age, he had another episode of hypoglycemic seizures following a similar fasting spell, and critical sample evaluation revealed similar findings. However, he did not have the classical cherubic facies associated with GSD type 1, and a repeat ultrasound abdomen showed normal-sized liver. Management: The clinical presentation and critical sample evaluation were suggestive of gluconeogenesis defect. However, the child did not have any other end-organ involvement. Hence, a possibility of FBPase deficiency was considered. The genetic testing confirmed compound heterozygous mutations involving the FBP1 gene. Conclusion: Fructose 1,6 bisphosphonate deficiency is a close mimicker of GSD 1.